Upaya Peningkatan Kinerja Belajar Mengajar Guru Melalui Supervisi Akademik Pada Pelaksanaan Manajemen Kepala Sekolah Di SMPN 13 - Sugiyarti, Sugiyarti (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
This study examines the managerial capabilities of school administration which emphasizes: the ability to develop learning tools, the ability to renew/innovate is a set of technical skills in an effort to carry out educational reform and teaching and learning processes in schools, in the context of carrying out school administration managerial tasks at least three kinds of skill areas, namely: technical, human and conceptual. The three school administration managerial skills vary according to the level of the manager's position in the organization. Managers can be divided into three levels, namely: top manager, middle manager and teacher manager. Likewise with this research, there are a number of benefits for both writers and readers. The impacts or benefits of this research are: (1) The results of this research are expected to be useful for developing educational administration disciplines, especially regarding teacher management at SMP Negeri 13 Kebayoran Baru, South Jakarta, (2) For the world of education in general, the results of this research are expected to be used as a reference as input for improving the quality of students in high schools, and the results of this study can be useful for teachers at SMP Negeri 13 Kebayoran Baru, South Jakarta in improving their performance.